Determinants of Exclusive Breastfeeding and Mixed Feeding Among Mothers of Infants in Dubai and Sharjah, United Arab Emirates - Haleama Al Sabbah; Enas A. Assaf; Zainab Taha; Radwan Qasrawi; Radwan Qasrawi; Hadia Radwan (Frontiers in Nutrition, 2022)
BackgroundBreastfeeding (BF) is considered the ultimate method of infant feeding for at least the first 6 months of life. Exclusive breastfeeding (EBF) is one of the most effective interventions to improve child survival. The main objective of this study was to assess the prevalence and duration of exclusive breastfeeding and the associated factors among women in Dubai and Sharjah, UAE.MethodsA cross-sectional study was conducted in four hospitals and four healthcare centers in Dubai and Sharjah between September 2017 and December 2017. Hospitals and centers are governmental and provide maternal and child health services. A convenience sample of 858 Arab and Emirati mothers with children under the age of 2 years participated in the study. Face-to-face interviews were conducted by using structured questionnaires. The study was approved by the University Ethical Committee and the UAE Ministry of Health before data collection. Descriptive statistics were computed to describe all the questionnaire items. The chi-square test was used to compare the study's categorical variables. A binary logistic regression analysis was used to predict the relationship between BF and its associated factors. Statistical tests with P-values < 0.05 were considered statistically significant.ResultsThe mean age of the participating mothers was 30.6 (SD 5.5) years. Results showed that the prevalence of exclusive breastfeeding among the study participants was 24.4% (31.1% in Sharjah and 22% in Dubai; P = 0.003). The binary logistic regression reported that mother's and father's education, skin-to-skin period, number of children, mothers' health, and place of living were significantly associated with exclusive breastfeeding (P < 0.05). The results reported a significant association between EB and duration of breastfeeding (OR = 6.9, P = 0.002), husband education (OR = 2.1, P = 0.015), mother education (OR = 1.3, P = 0.027), number of children (OR = 7.9, P = 0.045), having any health problem (OR = 1.2, P = 0.045), and living place (OR = 1.4, P = 0.033), and a non-significant positive effect of family size and family income. Furthermore, the result reported a significant association between mixed breastfeeding and duration of breastfeeding (OR = 0.1, P = 0.000), skin-to-skin period (OR = 0.3, P = 0.002), underweight (OR = 4.7, P = 0.034), last infant's sex (OR = 1.6, P = 0.010), having maid at home (OR = 2.1, P = 0.000), number of children (OR = 0.2, P = 0.013), and living place (OR =1.1, P = 0.014), and a non-significant association with family size and family income.ConclusionsTherefore, a health promotion program for exclusive breastfeeding during antenatal health visits, together with initiating health policies in maternal hospitals to encourage the initiation of breastfeeding during the first hour of birth and the introduction of skin-to-skin contact during the first 5 min of birth are highly recommended.